The Elemental Composition of Green Seaweed (Ulva rigida) Collected from Çanakkale, Turkey - Ekrem Cem Çankırılıgil; Nermin Berik (Aquatic Sciences and Engineering)
Seaweeds or marine algae are rich in terms of minerals. They are used as food source due to the quality of their biological content in many countries. In this study, the elemental composition of green seaweed (Ulva rigida) was determined seasonally. Sampling was carried out seasonally from Turkey’s Canakkale strait and the collected algae were analyzed both wet and dried according to the Nordic Committee on Food Analysis (method 186). According to the results; calcium, potassium, magnesium, sodium were found as macro elements and boron, barium, chromium, copper, iron, manganese, zinc as micro elements and determined within the legal limits stated by food codex. However, neither cobalt nor nickel as trace metals were detected in all groups. Moreover, lead and cadmium (which are considered hazardous) were also not detected. While Mg was found to be the highest macro element in all seasons in wet algae, the highest macro mineral varied in dried algae is Ca in spring, K in summer and Mg in both autumn and winter. Fe was found to be the highest micro mineral followed by B, Zn, Mn and Cu both by season and by dried or wet ones (P<0.05).